Passivity-Based PI Control Method of MMC with Asymmetric Bridge Arms - Cheng CHEN; Hua XUE; Zenghui HU; Yufei WANG (Zhongguo dianli)
Considering asymmetric bridge arms of modular multilevel converter (MMC), a passivity-based PI control method based on the bilinear model is proposed to address the dq decoupling transformation errors caused by the fundamental frequency component asymmetry of circulating currents,, which can achieve stable fault phase capacitor voltage, accurate suppression of asymmetric circulating current components and balanced output of three-phase grid-connected currents. Firstly the MMC bilinear model under the condition of asymmetric bridge arm is established in the abc coordinate. Then the linear transformation of the nonlinear system is conducted, in which the control variables are adjusted synchronously with the state variables. In this way the controller design is simplified and the control errors introduced by the dq decoupling transformation are diminished. Based on the global energy dissipation characteristics of the system, a simple passivity-based PI controller is designed to quickly suppress the sub-module capacitor voltage ripple, eliminate the current asymmetry of the bridge arm, and hence ensure the global asymptotically stable operation of the closed-loop control system. The simulation results based on MATLAB has verified that the proposed control method can effectively suppress the adverse effects from the asymmetric bridge arm, and exhibits its capability of fast response, strong stability and high robustness.